Comparative study of chitosan-based liquid dressing and recombinant human epidermal growth factor on acute limb skin wound healing: A randomized controlled trial - Dunyong Tan; Jiawei Guo; Xiaoqiang Chen; Jianquan Liu; Siyao Yang; Daping Wang; Wencui Li (JPRAS Open)
Abstracts: Background: Several traditional dressings may have limitation in treating wounds. A novel chitosan-based dressing designed for improved hemostasis, moisture, and sealing shows promise in wound healing. However, its efficacy and safety are yet to be sufficiently verified in patients. Methods: This randomized controlled trial enrolled 40 patients suffering from acute skin wounds in the limbs from 12/2022 to 12/2023. They were randomly divided into two groups (20 vs. 20) and received regular treatments in the Shenzhen Second People's Hospital. The experimental group was treated with chitosan-based liquid dressing, whereas the control group was treated with traditional dressing with recombinant human epidermal growth factor (rhEGF). The therapeutic effects (scar area and pigment deposition), adverse events, visual analogue scale (VAS), healing time, cost, and the patient and observer scar assessment scale (POSAS) were evaluated on days 0, 7, 14, and 28. Results: No adverse events were observed throughout the trial. On day 28, effective rate between groups were not statistically significant between the groups (70% vs. 85%, p = 0.256). Other parameters that were not significant included VAS (5.10 ± 1.62 vs. 6.35 ± 2.39, p = 0.06), healing time (8.45 ± 4.26 vs. 8.60 ± 5.44 days, p = 0.923), and cost (49.00 ± 22.48 vs. 57.40 ± 27.59, p = 0.298). However, on day 28, the patient- and observer-reported SAS of the chitosan (CS) group was significantly lower than that of the rhEGF group (12.00 vs. 9.50, z = 2.477, p = 0.013; 18.50 vs. 12.50, z = 2.209, p = 0.026; respectively), and the total POSAS (30.50 vs. 22.00, z = 2.374, p = 0.017). Conclusion: Compared to rhEGF, the CS-based liquid dressing showed reliable safety and equivalent performance in treating acute limb skin wounds, as revealed by improvements in healing time and rate, pain relief, and costs. Moreover, liquid dressing significantly reduced scar formation, indicating its potential in wound therapy.